2001
DOI: 10.1200/jco.2001.19.8.2319
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of 72-Hour Continuous Infusion UCN-01 in Patients With Refractory Neoplasms

Abstract: UCN-01 can be administered safely as an initial 72-hour CIV with subsequent monthly doses administered as 36-hour infusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
198
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(209 citation statements)
references
References 17 publications
9
198
2
Order By: Relevance
“…In summary, UCN-01 and VA, at clinically achievable drug concentrations and conditions (for instance 1.0 mM of VA and 500 nM of UCN-01) (Brodie and Dichter, 1996;Sausville et al, 2001), interact to mediate additive and supra-additive induction of apoptosis of cultured thoracic cancer cells. This chemosensitisation effect of UCN-0-1 in VA-treated cells is most likely secondary to its effect on downregulation of essential signal transduction pathways (PKC, ERK1/2, NF-kB) that regulate HDACI-induced apoptosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In summary, UCN-01 and VA, at clinically achievable drug concentrations and conditions (for instance 1.0 mM of VA and 500 nM of UCN-01) (Brodie and Dichter, 1996;Sausville et al, 2001), interact to mediate additive and supra-additive induction of apoptosis of cultured thoracic cancer cells. This chemosensitisation effect of UCN-0-1 in VA-treated cells is most likely secondary to its effect on downregulation of essential signal transduction pathways (PKC, ERK1/2, NF-kB) that regulate HDACI-induced apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…Exposure of cultured cancer cells to UCN-01 (250 -1000 nM) resulted in complete abrogation of phosphorylation at Ser473 and Thr308 residues of Akt, both of which are essential for full activation of Akt kinase activity (Amornphimoltham et al, 2004;Kondapaka et al, 2004). Clinical trials of UCN-01 in patients with refractory neoplasms, as monotherapy or in combination with cytotoxic chemotherapeutics, have been reported (Sausville et al, 2001). Continuous 72-h infusion of UCN-01 resulted in 'free' (after ultracentrifugation) plasma drug concentrations of 200 -600 nM and tissue drug concentration (via measurement of salivary UCN-01 concentrations as surrogates) of 110 nM (Sausville et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The phase I clinical trial did show evidence of activity in lymphomas, 28 with similar evidence reported in chronic lymphocytic leukemia (CLL) patients treated with a UCN-01 and fludarabine combination. 29 Depsipeptide derived from Chromobacterium violaceum, causes down-regulation of cyclin D1, up-regulation of cyclin E and p21-dependent cell cycle arrest at G 1 and G 2 .…”
Section: Spotlightmentioning
confidence: 62%
“…Frequent dosing is required to optimise the antitumour activity of UCN-01 , and 72 h of drug exposure is required to achieve growth inhibition. A Phase I trial of UCN-01 administered as a 72-h continuous infusion every 2 weeks to patients with advanced malignancy revealed long elimination half-lives due to high-affinity binding of UCN-01 to a1-acid glycoprotein in human plasma Sausville et al, 2001). This schedule was therefore changed to a 72-h continuous infusion administered every 4 weeks, with a recommended dose of 42.5 mg m 2 day À1 .…”
Section: Ucn-01mentioning
confidence: 99%